2016
DOI: 10.1111/hae.12951
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of non‐adherence to prescribed prophylactic clotting‐factor treatment regimens among adolescent and young adults with a bleeding disorder

Abstract: Results suggest that adherence efforts should be especially targeted to young adults as they transition from adolescence (i.e. parental supervision) and assume primary responsibility for their bleeding disorder care. Healthcare providers should be mindful of AYAs whose mothers have less formal education and ensure that adequate time and resources are dedicated to family adherence education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 29 publications
5
53
1
Order By: Relevance
“…VERITAS‐Pro thus allows to identify particular adherence issues and to distinguish between intentional and unintentional non‐adherence . Since its origin in the USA, VERITAS‐Pro has been used in various countries . However, as it assumes a compliant approach to adherence, it has not been found entirely applicable in health care settings with a more concordant treatment approach .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…VERITAS‐Pro thus allows to identify particular adherence issues and to distinguish between intentional and unintentional non‐adherence . Since its origin in the USA, VERITAS‐Pro has been used in various countries . However, as it assumes a compliant approach to adherence, it has not been found entirely applicable in health care settings with a more concordant treatment approach .…”
Section: Resultsmentioning
confidence: 99%
“…In a global survey, adherence dropped from 90% to 54% when 13‐18‐year‐olds started self‐infusing . In the USA, non‐adherence rose from 17% in 13‐17‐year‐olds to 47% in 18‐25‐year‐olds . It has been shown that up to 2/3 of YWH may experiment with stopping or reducing PTX …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…57 Myriad issues hinder adherence in adolescence and young adults including gaps in patient knowledge of the management of their bleeding disorder and product dosing/administration, self-infusion independence, coverage/payment for care, academic performance, employment opportunities, access to skilled adult care providers/centres, self and peer perception and parental ability to encourage independence. 57 Myriad issues hinder adherence in adolescence and young adults including gaps in patient knowledge of the management of their bleeding disorder and product dosing/administration, self-infusion independence, coverage/payment for care, academic performance, employment opportunities, access to skilled adult care providers/centres, self and peer perception and parental ability to encourage independence.…”
Section: Transitioning Teens To Adultsmentioning
confidence: 99%